Acrolein-mediated alpha-synuclein pathology involvement in the early post-injury pathogenesis of mild blast-induced Parkinsonian neurodegeneration - Acosta, Glen (Mol Cell Neurosci, 2019)
Survivors of blast-induced traumatic brain injury (bTBI) have increased susceptibility to Parkinson’s disease (PD), characterized by α-synuclein aggregation and the progressive degeneration of nigrostriatal dopaminergic neurons. Using an established bTBI rat model, we evaluated the changes of α-synuclein and tyrosine hydroxylase (TH), known hallmarks of PD, and acrolein, a reactive aldehyde and marker of oxidative stress, with the aim of revealing key pathways leading to PD post-bTBI. Indicated in both animal models of PD and TBI, acrolein is likely a point of pathogenic convergence. Here we show that after a single mild bTBI, acrolein is elevated up to a week, systemically in urine, and in whole brain tissue, specifically the substantia nigra and striatum. Acrolein elevation is accompanied by heightened α- synuclein oligomerization, dopaminergic dysregulation, and acrolein/α-synuclein interaction in the same brain regions. We further show that acrolein can directly modify and oligomerize α- synuclein in vitro. Taken together, our data suggests acrolein likely plays an important role in inducing PD pathology following bTBI by encouraging α-synuclein aggregation. These results are expected to advance our understanding of the long-term post-bTBI pathological changes leading to the development of PD, and suggest intervention targets to curtail such pathology.